Preharvest and postharvest treatments for increasing the rate of ripening of date palm fruit (Phoenix dactylifera L.) cv. Medjool: Ripening of date palm fruits - Kahramanoglu, Ibrahim; Usanmaz, Serhat (Progress in Nutrition, 2019)
Date palm (Phoenix dactylifera L.) is an important subsistence crop for regions having water scarcity problems, however it requires significant amount of heat for ripening of the fruits; and fruits do not ripen on the tree in some climatic regions. This study aimed to hasten the ripening process of date fruits cv. Medjool by some preharvest and postharvest applications. Three doses (500, 750 and 1,000 ppm) of Ethephon, two controls and apple vinegar (4-5% acidity) were used in the preharvest studies with or without bunch bagging (perforated black polyethylene bags). Postharvest experiments were conducted with visually mature firm (Khalal) fruits of the cv. Medjool, and are subjected to i-) dipping into distilled water; ii-) dipping into Ethephon 500 ppm; iii-) dipping into Ethephon 750 ppm; iv-) dipping into apple vinegar (4-5 % acidity); v-) dipping into grape vinegar (4-5 % acidity); and vi-) freezing at -18ÅãC for 3 days. Results showed that bunch bagging enhances fruit ripening on the tree, increase fruits’ total soluble solids (TSS) and reduce titratable acidity (TA) at both Tamr and Khalal stages. Preharvest application of 1,000 ppm Ethephon (with bunch bagging) found to have highest ratio of Tamr (37%) and Rutab (46%) fruits where preharvest apple vinegar application had slight effect on the fruit ripening (12% Tamr) as compared with control (8% Tamr). On the other hand, postharvest application of apple vinegar, freezing at -18ÅãC and grape vinegar found to enhance fruit ripening and the percentage of Tamr fruits were determined as 100%, 100% and 92% respectively.